2001
DOI: 10.1001/archsurg.136.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gallstone Cholangitis in the Era of Laparoscopic Cholecystectomy

Abstract: Hypothesis: The combined endoscopic and laparoscopic approach is safe and effective in managing gallstone cholangitis in the era of laparoscopic cholecystectomy (LC). Design: Retrospective case series. Setting: University teaching hospital. Patients: One hundred eighty-four consecutive patients with gallstone cholangitis treated between January 1995 and December 1998. Interventions: The main treatments were endoscopic retrograde cholangiopancreatography (ERCP) and endoscopic sphincterotomy (ES) followed by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…In conclusion, endoscopic assessment of the bile duct should be performed only in patients with a high risk of having bile duct stones. In agreement with other findings [20,22,27], our data show that patients with acute cholangitis are those who have a high risk of harboring bile duct stones.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In conclusion, endoscopic assessment of the bile duct should be performed only in patients with a high risk of having bile duct stones. In agreement with other findings [20,22,27], our data show that patients with acute cholangitis are those who have a high risk of harboring bile duct stones.…”
Section: Discussionsupporting
confidence: 93%
“…In 1977, good results were already being obtained when endoscopic decompression was employed for the management of a particular form of cholangitis, known as "supurative cholangitis" [14], more recently, a randomized trial showed better results after endoscopic biliary drainage followed by definitive treatment than after surgical decompression [13]. An aggressive policy of early endoscopic biliary drainage resulted in a very low mortality rate [22]. On the other hand, delay in ERCP for patients with severe cholangitis resulted in increased mortality and morbidity [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, patients with larger CBD stones also are those in whom ERCP/ES most frequently fails, as observed in our experience, and those best served by a choledochotomy with a T-tube. Furthermore, patients with gallbladder left in situ after endoscopic sphincterotomy have an increased risk of recurrent biliary symptoms, which have been reported to occur in 25% of cases [17].…”
Section: Discussionmentioning
confidence: 99%
“…If a patient has had an endoscopic sphincterotomy during the course of an attack of gallstone-associated acute pancreatitis consideration should be given to removing the gallbladder as these patients have a relatively high risk of subsequent gallbladder symptoms [70][71][72][73][74].…”
Section: Gallstone-associated Acute Pancreatitismentioning
confidence: 99%